DEVELOPMENT OF ETHNOSAINS-BASED IPA MODULE IN THEME DIVERSITY THROUGH LIVING INTEGRATED EDUCATION CHARACTERS OF CLASS VII SMP - ella vriwista; Tuti Lestari (Department of Science Education, 2021)
The challenge in the science learning process that is often encountered is the independence of student learning and the weak preservation of the existing culture in the surrounding environment as a source of learning is still weak. Through the ethnoscience-based science module students will be able to learn independently in the environment where the student lives. Independent study in a residential environment will be able to form the character of students because they are immediately one with nature. The type of research used is Research and Development (R & D) using a 4-D model which consists of four stages, namely the Define, Design, Develop, and Dessiminate stages. This research is limited only to the develop stage, the dessiminate stage was not carried out due to time and cost limitations. The results of the analysis of the teacher's validity and practicality sheet showed that the average kappa moment score (k) was 0.81 and 0.90, respectively, with the very valid and practical categories. The data obtained shows that the ethnoscience-based Science Module on the theme of integrated living diversity character education for grade VII SMP is valid and practical.